SARS-CoV-2 infection does not induce HIV viral escape in the central nervous system: A case series. (December 2020) - Pinnetti, C.; Vergori, A.; Agrati, C.; Castilletti, C.; Campioni, P.; Gagliardini, R.; Mondi, A.; Notari, S.; Amendola, A.; Cicalini, S.; Baldini, F.; Capobianchi, M.R.; et al.
Highlights: The impact of co-infection with SARS-CoV-2 on HIV replication in the central nervous system (CNS) is unknown. SARS-CoV-2 could alter the permeability of the blood–brain barrier and cause a CNS HIV escape. The few symptoms during coronavirus disease 2019 (COVID-19) suggest a contained inflammatory response in CNS/plasma. Poor immunological recovery might contribute to soften immune-pathogenetic processes. Abstract: We report two cases of HIV positive patients with SARS-CoV-2 infection and a recent diagnosis of opportunistic infections of central nervous system (CNS). We investigated the potential impact of coinfection with SARS-CoV-2 on HIV replication in CNS.